A caderneta de saúde da criança na percepção dos profissionais que atuam na rede básica de saúde de Cuiabá/MT - Silva, Fabiane Blanco e (2014)
The child health handbook is an instrument which aims the integral monitoring of child health, based on health surveillance. In Brazil, this instrument is configured as the main document for the information of child's health and also serves as a tool for dialogue between families and the professionals who work in different spaces for assistance to this population. This study aims to analyze the perceptions of professionals working in child care in basic health network of Cuiabá – Mato Grosso, on the use of child health handbook. This is an exploratory study of qualitative approach, which had as its subject eight doctors, eight nurses and four community health agents, totaling 20 professionals who acted in basic health units of this municipality. The data collection was carried out from February to March 2013, through a semi-structured interview, analyzed by the technique of thematic analysis. The data analysis allowed the grouping of information in three thematic axes: the several purposes of maternal and child health; the fill of the child health handbook by the professionals and the use of the child health handbook by the family. The professionals attach to the booklet the interpretation that it is an important document because it contains various information of child health, even before his birth. In addition, there are different opinions about the purpose of the same. Regarding the data to be filled in the document, the professionals refer to be important for the monitoring of children's health, however, for them the record of those still does not receive due weight in all attendances to the child. For professionals the padding of the data is of the responsibility of the health team, doctor, nurse and nursing technicians. There was disagreement of opinion on the participation of the family in this fill, and for some the family must not fill any data, while for other identification data, development and complications with the child can be registered by the family. There are many factors that influence the use of booklet by professionals such as loss or forgetfulness of the instrument by her mother, bureaucracy, high demand for service activities in the unit, among others. In the perception of the participants of the study, although the family be oriented about the booklet, the same still uses very little. For the interviewees, beyond the family having the right to ask for registration data from the professionals in the booklet, this family's behavior demonstrates its interest in the health of the child and assists the work of professionals. It is noted, also, a concern of the participants of the study regarding the full use of the notebook. Thus, for this instrument being effective such as surveillance and promotion document to child health both the professionals and the families should assign more value to it.